Introduction to nonprofit management : text and cases - Dato-on, Mary Conway; Rowe, W. Glenn (The Ivey casebook series, 2013)
The casebook helps students gain a better understanding of nonprofit management by providing 28 contemporary cases from around the world, illustrating the complexity of nonprofit management in a variety of different sectors